Hit makers how things become popular - Thompson, Derek (London Allen Lane, 2017)
Drawing on ancient history and modern headlines - from vampire lore and Brahms's Lullaby to Instagram - Thompson explores the economics and psychology of why certain things become extraordinarily popular. With incisive analysis and captivating storytelling, he reveals that, though blockbuster films, Internet memes and number-one songs seem to have come out of nowhere, hits actually have a story and operate by certain rules. People gravitate towards familiar surprises: products that are bold and innovative, yet instantly comprehensible.
Includes bibliographical references and index.
Keywords: SOCIAL SCIENCE / Anthropology / Cultural & Social; Consumption (Economics); Popularity -- Social aspects; Marketing -- Social aspects; SOCIAL SCIENCE / Popular Culture; Popular Culture